Arthrobacter nitrophenolicus sp. nov. a new 2-chloro-4-nitrophenol degrading bacterium isolated from contaminated soil - Arora, Pankaj Kumar (Springer Berlin Heidelberg, 2012)
Strain SJCon(T), a 2-chloro-4-nitrophenol (2C4NP) degrading bacterium, was isolated from soil collected from a pesticide-contaminated site in Punjab, India. The strain, which stained Gram positive, displayed a rod-coccus life cycle, and possessed a type A3(α) peptidoglycan (l-Lys–l-Ala(3)), MK-9(H2) as the major menaquinone, anteiso-C15 and iso-C15:0 as the major cellular fatty acids, and diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol and a glycolipid as the major polar lipids, showed morphological and chemotaxonomic properties consistent with those reported for members of the genus Arthrobacter. Phylogenetic analysis of the 16S rRNA gene sequence of strain SJCon(T) confirmed that it was a member of this genus with Arthrobacter globiformis DSM 20124(T) being the closest relative (sequence similarity of 97 %). The DNA G + C content of strain SJCon(T) was 69 ± 1 mol% and DNA homology with A. globiformis DSM 20124(T) was 45 %, suggesting that strain SJCon(T) represented a novel species of the genus Arthrobacter, which we have named Arthrobacter nitrophenolicus sp. nov The type strain is SJCon(T) (=MTCC 10104(T) =DSM 23165(T)).